High‐Ranged ZT Value Promotes Thermoelectric Cooling and Power Generation in n‐Type PbTe. Issue 16 (13th March 2022) - Xiao, Yu; Wu, Haijun; Shi, Haonan; Xu, Liqing; Zhu, Yuke; Qin, Yongxin; Peng, Guyang; Zhang, Yang; Ge, Zhen‐Hua; Ding, Xiangdong; Zhao, Li‐Dong
Abstract: Excellent thermoelectric cooling and power generation are simultaneously realized in an n‐type PbTe‐based thermoelectric material. The cooling temperature difference (Δ T ) of ≈15.6 K, maximum power density of ≈0.4 W cm −2 and conversion efficiency of ≈1.5% with T C  = 295 K and T H  = 765 K can be obtained in a single‐leg device composed of PbTe‐30%SnSe‐1.5%Cu. This advanced thermoelectric performance in n‐type PbTe‐30%SnSe‐1.5%Cu mainly originates from its high‐ranged ZT value achieved through optimizing its bandgap, carrier density, and microstructure. The bandgap in PbTe is first reduced by SnSe alloying to facilitate the carrier transport properties at low temperature range (300–573 K). With further tuned carrier density, the average power factor increases from ≈10.2 µW cm −1 K −2 in Pb0.985 Sb0.015 Te‐30%SnSe to ≈16.2 µW cm −1 K −2 in PbTe‐30%SnSe‐1.5%Cu at 300–773 K. Moreover, microstructure observation reveals high‐density dislocations in PbTe‐30% SnSe‐1.5% Cu, which can dramatically suppress the room‐temperature lattice thermal conductivity from ≈2.21 Wm −1  K −1 in Pb0.985 Sb0.015 Te to ≈0.53 Wm −1  K −1 in PbTe‐30%SnSe‐1.5%Cu. As a result, a room‐temperature ZT value of ≈0.7 and high average ZT value ( ZT ave ) of ≈0.98 can be obtained in PbTe‐30%SnSe‐1.5%Cu at 300–573 K, which makes its performance comparable to the commercial n‐type Bi2 Te3 ‐based thermoelectric material. Abstract : The near‐room‐temperature thermoelectric performance in n‐type PbTe is enhanced through band sharpening and dynamic doping. With the optimized triple relations between carrier effective mass, carrier density, and lattice thermal conductivity, a room‐temperature ZT value of ≈0.7 and high average ZT value of ≈0.98 are obtained in PbTe‐30%SnSe‐1.5%Cu at 300–573 K.